Solid plastic crystal electrolyte and preparation method and application thereof
Through the in-situ polymerization process of solid-state plastic crystalline electrolyte, the price fluctuations in traditional lithium-ion battery raw materials and the safety hazards of liquid electrolytes are solved, and the high performance and high safety of sodium metal batteries are achieved.
Patent Information
- Application Number
- CN202411583124.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The raw materials prices of traditional lithium-ion batteries fluctuate greatly, and liquid electrolytes have safety hazards and battery performance attenuation problems, limiting the large-scale application of solid electrolytes.
Using solid plastic crystalline electrolyte, the succinitrile monomer is mixed with sodium salt and fluorovinyl carbonate through in-situ polymerization process to form a polymer network, covering the deep eutectic electrolyte to avoid succinitrile and sodium metal Negative contact.
The excellent rate performance and long cycle stability of sodium metal batteries are achieved, the interface resistance is reduced, the formation of sodium dendrites is suppressed, and the high safety performance and high ionic conductivity of the battery are ensured.
Smart Images

Figure CN119419351A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state sodium metal batteries and electrochemical technology, and specifically relates to a solid-state plastic crystal electrolyte and a preparation method and application thereof. Background Art
[0002] Traditional lithium-ion battery systems have been widely used in electric vehicles and portable electronic devices due to their many advantages, such as high energy density, excellent cycle performance, high output power, and long life. However, due to the uneven distribution of lithium mineral resources around the world and their relatively low reserves (approximately 0.0065% of the earth's crust), the price of raw materials for lithium-ion batteries fluctuates greatly, which in turn makes the cost of lithium battery energy storage systems remain high. Sodium accounts for more than 2.6% of the earth's crust, ranking 11th among all elements in the earth's crust. Therefore, the cost of the sodium battery system will be far superior to that of the lithium battery system. In the field of large-scale energy storage, the sodium battery system has shown a very broad application prospect. As the negative electrode of the energy storage battery, sodium metal can provide a low reduction potential and a high capacity of up to 1166mAh g -1 Theoretical specific capacity. However, the use of traditional liquid electrolytes presents serious safety hazards and will cause serious degradation of battery performance. First, in the currently commercially available ester electrolytes, the solution components are volatile and easy to burn. When the battery is damaged by external forces, the electrolyte is easy to leak out of the battery body, causing environmental pollution and safety problems. Secondly, traditional inorganic solid electrolytes and organic electrolytes also have problems such as large electrode / electrolyte interface impedance and low ionic conductivity, which restrict the large-scale application of solid electrolytes. In addition, gel electrolytes are between all-solid electrolytes and liquid electrolytes. While ensuring good compatibility at the electrode / electrolyte interface, they have high ionic conductivity, but because they still contain electrolyte components, they have certain safety hazards. Summary of the invention
[0003] In order to solve the above safety problems caused by electrolytes, the present invention provides a solid plastic crystal electrolyte, which is an electrolyte that uses succinonitrile monomers to replace the ester solvent components in traditional electrolytes. The present invention provides a method for preparing solid plastic crystal batteries by in-situ polymerization. In-situ polymerization refers to injecting a liquid electrolyte precursor into a diaphragm, heating the battery after the battery is assembled, and the liquid precursor undergoes a solidification process under the action of an initiator and high temperature. The solid electrolyte prepared by the in-situ polymerization process has the characteristics of good contact between the liquid electrolyte and the electrode interface and the high safety characteristics of the solid electrolyte. The present invention uses a polymer network to coat the deep eutectic electrolyte, and the functional groups (C=O, CO) on the polymer chain segments and the free succinonitrile molecules achieve an "anchoring" effect through electrostatic force, avoiding the performance deterioration caused by the contact between succinonitrile and the metal sodium negative electrode. The sodium metal battery using this solid electrolyte exhibits excellent rate performance and outstanding cycle stability. The present invention is of great significance to the application of high-safety plastic crystal electrolytes and broadens the application of solid plastic crystal electrolytes in sodium battery systems.
[0004] The technical solution of the present invention is as follows:
[0005] A solid plastic crystal electrolyte mainly consists of two phases: the first phase is a plastic crystal phase composed of succinonitrile, sodium salt and fluoroethylene carbonate additives; the second phase is a polymer network phase formed by mixing two double bond monomers in proportion; the two phases are mixed in a certain proportion and in-situ cured under the action of an initiator and heating.
[0006] In the first phase, the concentration of sodium salt in succinonitrile is 0.8-1.5ML -1 ; The volume fraction of fluoroethylene carbonate is 5%-10%.
[0007] The volume ratio of the two monomers having double bonds is 1:1-1:5.
[0008] The volume ratio of the first phase to the second phase is 9:1-5:5.
[0009] The sodium salt is one or a mixture of two or more of sodium bis(trifluoromethylsulfonyl)imide, sodium perchlorate and sodium hexafluorophosphate.
[0010] The double bond monomer is a double bond monomer with difunctionality, trifunctionality or tetrafunctionality.
[0011] The double bond monomer is ethoxylated trimethylolpropane triacrylate monomer, polyethylene glycol diacrylate, ethylene glycol dimethacrylate or pentaerythritol tetraacrylate monomer.
[0012] The preparation method of the solid plastic crystal electrolyte comprises the following specific steps:
[0013] Step (1) Succinonitrile and sodium salt are mixed in proportion, heated and stirred, and after stirring until a clear and transparent liquid is obtained, fluoroethylene carbonate is added to obtain a solution A;
[0014] Step (2) degassing solution A to remove oxygen to obtain solution B, i.e., the first phase;
[0015] Step (3) mixing the two double bond monomers in proportion and stirring until a clear and transparent uniform solution is obtained to obtain solution C, i.e., the second phase;
[0016] Step (4) After mixing solution B and solution C in proportion, an initiator is added and stirred until the whole solution becomes clear and transparent, thereby obtaining solution D;
[0017] Step (5) Inject solution D as a precursor solution into both sides of the battery separator when assembling the battery, heat the assembled battery at 60-75°C for 2-4h to completely solidify the liquid precursor inside the battery, and obtain a solid plastic crystal electrolyte.
[0018] In the step (2), solution A is subjected to 3-5 freeze-thaw cycles for degassing.
[0019] In the step (4), the mass of the initiator is 0.5-1% of the mass of solution C.
[0020] In the step (5), the electrolyte precursor solution is dripped onto both sides of the diaphragm twice to completely soak the diaphragm.
[0021] The initiator is one or a mixture of two or more of tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile.
[0022] The solid plastic crystal electrolyte prepared by the above method is used in sodium metal batteries, which can effectively reduce the interface resistance of traditional solid electrolytes, inhibit the formation of dendrites at the interface of sodium metal negative electrode, and improve its electrochemical performance.
[0023] Beneficial effects of the present invention:
[0024] (1) The in-situ curing process ensures close contact between the electrolyte / interface and reduces the charge transfer resistance at the interface.
[0025] (2) The existence of the polymer network has an anchoring effect on the free succinonitrile monomers through electrostatic force, and the solid electrolyte has a good inhibitory effect on the formation of sodium dendrites, ensuring that there is no obvious capacity decay after long-term cycling of the sodium metal battery.
[0026] (3) The electrolyte components are inherently non-flammable and non-volatile. When ignited by an open flame, the electrolyte itself will not burn, ensuring the high safety performance of the battery.
[0027] (4) The ionic conductivity of the electrolyte at room temperature is greater than 1 mS cm -1 ,The high ionic conductivity ensures the excellent rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the structure of the solid-state plastic crystal sodium metal battery of the present invention;
[0029] Figure 2 Schematic diagram of the interaction between the cross-linked polymer network and the free succinonitrile monomer in the present invention;
[0030] Figure 3 is a linear voltammetric scan curve of the electrolyte prepared in Example 2 of the present invention;
[0031] Figure 4 is an FT-IR scan of the electrolyte prepared in Example 3 of the present invention;
[0032] Figure 5 is the cycle performance of the full battery prepared in Example 1 of the present invention;
[0033] Figure 6 is a charge and discharge curve diagram of the full battery prepared in Example 4 of the present invention;
[0034] Figure 7 This is a rate performance diagram of the full battery prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0035] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0036] Embodiment 1:
[0037] (1) Place 1 g of succinonitrile and 0.24 g of sodium bis(trifluoromethylsulfonyl)imide in a sample bottle.
[0038] (2) Place the sample bottle on a hot plate and heat it at 70°C with magnetic stirring at a speed of 300 r / min. Heat and stir for 2 h until the succinonitrile solid completely turns into liquid and the sodium salt is completely dissolved.
[0039] (3) Use a pipette to transfer 50 μL of fluoroethylene carbonate into the above solution and then stir magnetically for 1 h.
[0040] (4) Use a pipette to transfer 50 μL of ethoxylated trimethylolpropane triacrylate and 50 μL of ethylene glycol dimethacrylate into a sample bottle, and stir magnetically at room temperature at a speed of 300 r / min until the solution becomes homogeneous.
[0041] (5) After the above solutions are mixed evenly, 0.001 g of azobisisobutyronitrile is added and stirred until the solid particles are completely dissolved to obtain a solid electrolyte precursor solution.
[0042] (6) Sodium vanadium phosphate, a conductive agent, and a binder are ground in a ratio of 8:1:1, and an appropriate amount of NMP is added for auxiliary grinding to form a uniformly dispersed slurry. An appropriate amount of the slurry is coated on an aluminum foil using a coating machine, and then placed in a vacuum oven for drying to obtain a positive electrode sheet.
[0043] (7) The positive electrode sheet prepared in the previous step is sliced into a certain size to make a positive electrode sheet, and the positive electrode sheet and the sodium metal sheet are used to assemble a CR2032 button battery. During the assembly, the solid electrolyte precursor solution prepared in step (5) is added dropwise.
[0044] (8) The assembled battery was placed in an oven for heating and curing. The oven temperature was set to 70°C and the heating time was 4 h.
[0045] Figure 5 The full battery prepared in this example was subjected to a long cycle test at a rate of 2C (1C = 100 mAh g -1 ), a long cycle test was carried out at a rate of 2C. The battery capacity did not decay significantly after 200 cycles, and the coulombic efficiency was greater than 99.5%. The electrochemical performance of this electrolyte is stable, and the deep eutectic electrolyte locked by the polymer network has excellent performance.
[0046] Embodiment 2:
[0047] (1) Place 2 g of succinonitrile and 0.6 g of sodium bis(trifluoromethylsulfonyl)imide in a sample bottle.
[0048] (2) Place the sample bottle on a hot plate and heat it at 80°C with magnetic stirring at a speed of 300 r / min. Heat and stir for 2 h until the succinonitrile solid completely turns into liquid and the sodium salt is completely dissolved.
[0049] (3) Use a pipette to transfer 200 μL of fluoroethylene carbonate into the above solution and then stir magnetically for 1 h.
[0050] (4) Use a pipette to transfer 120 μL of polyethylene glycol diacrylate and 360 μL of ethylene glycol dimethacrylate into a sample bottle, and stir magnetically at room temperature at a speed of 300 r / min until the solution becomes homogeneous.
[0051] (5) After the above solutions are mixed evenly, 0.002 g of azobisisoheptanenitrile is added and stirred until the solid particles are completely dissolved to obtain a solid electrolyte precursor solution.
[0052] (6) The obtained precursor solution is injected into a half-cell, wherein the negative electrode of the half-cell is a sodium metal sheet and the positive electrode is a stainless steel sheet.
[0053] (7) The assembled battery was placed in an oven for heating and curing. The oven temperature was set to 70°C and the heating time was 4 h.
[0054] Figure 3 This is the linear voltammetric scan of the half-cell assembled in this example, with a scan rate of 0.1 mV S -1 When the applied voltage is less than 4.2 V, there is no obvious response current, which indicates that the electrolyte has a wide electrochemical window and meets the requirements of sodium metal batteries.
[0055] Embodiment 3:
[0056] (1) Place 0.5 g of succinonitrile and 0.07 g of sodium perchlorate in a sample bottle.
[0057] (2) Place the sample bottle on a hot plate and heat it at 75°C with magnetic stirring at a speed of 300 r / min. Heat and stir for 2 h until the succinonitrile solid completely turns into liquid and the sodium salt is completely dissolved.
[0058] (3) Use a pipette to transfer 500 μL of fluoroethylene carbonate into the above solution and then stir magnetically for 1 h.
[0059] (4) Use a pipette to transfer 80 μL of ethoxylated trimethylolpropane triacrylate and 400 μL of ethylene glycol dimethacrylate into a sample bottle, and stir magnetically at room temperature at a speed of 300 r / min until the solution becomes homogeneous.
[0060] (5) After the above solutions are mixed evenly, 0.01 g of tert-butyl hydroperoxide is added and stirred until the solid particles are completely dissolved to obtain a solid electrolyte precursor solution.
[0061] (6) Sodium vanadium phosphate, a conductive agent, and a binder are ground in a ratio of 8:1:1, and an appropriate amount of NMP is added for auxiliary grinding to form a uniformly dispersed slurry. An appropriate amount of the slurry is coated on an aluminum foil using a coating machine, and then placed in a vacuum oven for drying to obtain a positive electrode sheet.
[0062] (7) The positive electrode sheet prepared in the previous step is sliced into a certain size to make a positive electrode sheet, and the positive electrode sheet and the sodium metal sheet are used to assemble a CR2032 button battery. During the assembly, the solid electrolyte precursor solution prepared in step (5) is added dropwise.
[0063] (8) The assembled battery is placed in an oven for heating and curing. The oven temperature is set to 80°C and the heating time is 6 hours. After heating, a solid-state sodium metal battery is obtained.
[0064] Figure 4 This is the FT-IR scan of the electrolyte in this embodiment. From the peak position, it can be seen that the stretching vibration peak positions of the C=C bond and the C=O bond in the ethoxylated trimethylolpropane triacrylate monomer and the ethylene glycol dimethacrylate monomer are obvious, and the stretching vibration peak position of the CN group of the succinonitrile monomer is obvious. However, in the solid plastic crystal electrolyte after polymerization, the C=C bond completely disappears, proving that the free radical polymerization reaction of the two monomers has successfully occurred. At the same time, the strength of the C=O bond has not been significantly reduced, indicating that the polymerization process does not affect the C=O bond. In the final product, the solid plastic crystal electrolyte, the peak position of the CN group is obvious, proving that the succinonitrile monomer is well retained in the solid plastic crystal electrolyte.
[0065] Embodiment 4:
[0066] (1) Place 10 g of succinonitrile and 3 g of sodium bis(trifluoromethylsulfonyl)imide in a sample bottle.
[0067] (2) Place the sample bottle on a hot plate and heat it at 70°C with magnetic stirring at a speed of 300 r / min. Heat and stir for 2 h until the succinonitrile solid completely turns into liquid and the sodium salt is completely dissolved, with no solid phase remaining.
[0068] (3) Use a pipette to transfer 1 ml of fluoroethylene carbonate into the above solution and then stir magnetically for 1 h.
[0069] (4) Use a pipette to transfer 1000 μL of ethoxylated trimethylolpropane triacrylate and 400 μL of ethylene glycol dimethacrylate into a sample bottle, and stir the mixture with a magnetic stirrer at room temperature at a speed of 300 r / min until the solution becomes homogeneous.
[0070] (5) After the above solutions are mixed evenly, 0.01 g of azobisisobutyronitrile is added and stirred until the solid particles are completely dissolved to obtain a solid electrolyte precursor solution.
[0071] (6) Sodium vanadium phosphate, a conductive agent, and a binder are ground in a ratio of 8:1:1, and an appropriate amount of NMP is added for auxiliary grinding to form a uniformly dispersed slurry. An appropriate amount of the slurry is coated on an aluminum foil using a coating machine, and then placed in a vacuum oven for drying to obtain a positive electrode sheet.
[0072] (7) The positive electrode sheet prepared in the previous step is sliced into a size of 4.5×5.5 cm to make a positive electrode sheet, and the positive electrode sheet and a sodium metal sheet of 4.5×5.5 cm are used to assemble a soft-pack battery. During the assembly, the solid electrolyte precursor solution prepared in step (5) is added dropwise.
[0073] (8) The assembled battery was placed in an oven for heating and curing. The oven temperature was set to 70°C and the heating time was 4 h.
[0074] Figure 6 The charge and discharge curves of the full battery prepared in this embodiment are as follows. At the discharge rates of 0.5C, 1C, 2C, 3C and 5C, 92.23 mAh g -1 , 89.97mAh g -1 , 84.02mAh g -1 , 77.97mAh g -1 and 64.45mAh g -1 The discharge capacity.
[0075] Example 5
[0076] (1) Place 7 g of succinonitrile and 2.1 g of sodium hexafluorophosphate in a sample bottle.
[0077] (2) Place the sample bottle on a hot plate and heat it at 70°C with magnetic stirring at a speed of 300 r / min. Heat and stir for 2 h until the succinonitrile solid completely turns into liquid and the sodium salt is completely dissolved.
[0078] (3) Use a pipette to transfer 700 μL of fluoroethylene carbonate into the above solution and then stir magnetically for 1 h.
[0079] (4) Use a pipette to transfer 500 μL of ethoxylated trimethylolpropane triacrylate and 320 μL of ethylene glycol dimethacrylate into a sample bottle, and stir magnetically at room temperature at a speed of 300 r / min until the solution becomes homogeneous.
[0080] (5) After the above solutions are mixed evenly, 0.01 g of azobisisobutyronitrile is added and stirred until the solid particles are completely dissolved to obtain a solid electrolyte precursor solution.
[0081] (6) Sodium vanadium phosphate, a conductive agent, and a binder are ground in a ratio of 8:1:1, and an appropriate amount of NMP is added for auxiliary grinding to form a uniformly dispersed slurry. An appropriate amount of the slurry is coated on an aluminum foil using a coating machine, and then placed in a vacuum oven for drying to obtain a positive electrode sheet.
[0082] (7) The positive electrode sheet prepared in the previous step is sliced into a certain size to make a positive electrode sheet, and the positive electrode sheet and the sodium metal sheet are used to assemble a CR2032 button battery. During the assembly, the solid electrolyte precursor solution prepared in step (5) is added dropwise.
[0083] (8) The assembled battery was placed in an oven for heating and curing. The oven temperature was set to 70°C and the heating time was 4 h.
[0084] Figure 7 The full battery prepared in this example was subjected to a charge and discharge test at a high rate to evaluate the rate performance of the battery. At a charge and discharge rate of 5C, the battery's discharge capacity was 85.46 mAh g -1 At a rate of 10C, the discharge capacity of the battery is 74.62 mAh g -1 At a rate of 15C, the discharge capacity of the battery is 73.64 mAh g -1 At a high rate of 20C, the discharge capacity of the battery is still greater than 35 mAh g -1 . It has practical significance for application at high magnification.
Claims
1. A solid plastic crystal electrolyte, characterized in that: The solid plastic crystal electrolyte is mainly composed of two phases: the first phase is a plastic crystal phase composed of succinonitrile, sodium salt and fluoroethylene carbonate additive; the second phase is a polymer network phase formed by mixing two double bond monomers in proportion; the two phases are mixed in a certain proportion and in situ cured under the action of an initiator and heating; In the first phase, the concentration of sodium salt in succinonitrile is 0.8-1.5ML -1 ; The volume fraction of fluoroethylene carbonate is 5%-10%; The volume ratio of the two monomers having double bonds is 1:1-1:5; The volume ratio of the first phase to the second phase is 9:1-5:
5.
2. A solid plastic crystal electrolyte according to claim 1, characterized in that: The sodium salt is one or a mixture of two or more of sodium bis(trifluoromethylsulfonyl)imide, sodium perchlorate and sodium hexafluorophosphate.
3. A solid plastic crystal electrolyte according to claim 1 or 2, characterized in that: The double bond monomer is a double bond monomer with difunctionality, trifunctionality or tetrafunctionality.
4. A solid plastic crystal electrolyte according to claim 3, characterized in that: The double bond monomer is ethoxylated trimethylolpropane triacrylate monomer, polyethylene glycol diacrylate, ethylene glycol dimethacrylate or pentaerythritol tetraacrylate monomer.
5. The method for preparing the solid plastic crystal electrolyte according to any of claims 1 to 4, characterized in that: The specific steps are as follows: Step (1) Succinonitrile and sodium salt are mixed in proportion, heated and stirred, and after stirring until a clear and transparent liquid is obtained, fluoroethylene carbonate is added to obtain a solution A; Step (2) degassing solution A to remove oxygen to obtain solution B, i.e., the first phase; Step (3) mixing the two double bond monomers in proportion and stirring until a clear and transparent uniform solution is obtained to obtain solution C, i.e., the second phase; Step (4) After mixing solution B and solution C in proportion, an initiator is added and stirred until the whole solution becomes clear and transparent, thereby obtaining solution D; Step (5) Inject solution D as a precursor solution into both sides of the battery separator when assembling the battery, heat the assembled battery at 60-75°C for 2-4h to completely solidify the liquid precursor inside the battery, and obtain a solid plastic crystal electrolyte.
6. The method for preparing the solid plastic crystal electrolyte according to claim 5, characterized in that: In the step (2), solution A is subjected to 3-5 freeze-thaw cycles for degassing.
7. The method for preparing the solid plastic crystal electrolyte according to claim 5 or 6, characterized in that: In the step (4), the mass of the initiator is 0.5-1% of the mass of solution C.
8. The method for preparing the solid plastic crystal electrolyte according to claim 5 or 6, characterized in that: In the step (5), the electrolyte precursor solution is dripped onto both sides of the diaphragm twice to completely soak the diaphragm.
9. The method for preparing the solid plastic crystal electrolyte according to claim 5 or 6, characterized in that: The initiator is one or a mixture of two or more of tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile.
10. The solid plastic crystal electrolyte prepared by any method described in claims 5-9 is used in sodium metal batteries.
Citation Information
Cited By
Environment-friendly eutectic cellulose quasi-solid electrolyte capable of being thermally polymerized in situ and preparation method of environment-friendly eutectic cellulose quasi-solid electrolyte
CN121584017A